Correction: Efficient dye-sensitized solar cells with broad absorption and enhanced photo-current generation. Issue 71 (13th July 2016) - Kim, Jihun; Lee, Horim; Kim, Dong Young; Seo, Yongsok
Abstract : Correction for 'Efficient dye-sensitized solar cells with broad absorption and enhanced photo-current generation' by Jihun Kim et al., RSC Adv., 2016, 6, 56747–56755.